Conductive liquid crystal resin composition

By adding an appropriate amount of fiber-like and granular conductive filler and non-conductive filler to the liquid crystal resin, the problems of poor forming processability and large fluctuation of volume resistivity of the liquid crystal resin composition are solved, and the effects of excellent forming processability and low volume resistivity are achieved.

CN116601230BActive Publication Date: 2025-04-18POLYPLASTICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180081329.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-07
Filing Date
2021-12-02
Publication Date
2025-04-18
Estimated Expiration
2041-12-02

AI Technical Summary

Technical Problem

The conventional liquid crystal resin composition has a high volume resistivity, high melt viscosity, insufficient forming processability, and difficult to form into a complex shape, and the volume resistivity varies greatly when the thickness changes.

Method used

The composition containing a liquid crystal resin, a fibrous conductive filler, a particulate conductive filler and a non-conductive filler is used. The total content of the fibrous conductive filler and a particulate conductive filler is between 25 and 50 mass%, the mass ratio of the fibrous conductive filler and a particulate conductive filler is between 0.50 and 3.00, and the content of the non-conductive filler is between 2 and 8 mass%.

Benefits of technology

It has achieved excellent forming processability, low volume resistivity, and small variation in volume resistivity regardless of thickness, and is suitable for products of complex shapes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004263394960000041
    Figure BDA0004263394960000041
  • Figure BDA0004263394960000051
    Figure BDA0004263394960000051
  • Figure BDA0004263394960000131
    Figure BDA0004263394960000131
Patent Text Reader

Abstract

Provided is a conductive liquid crystal resin composition that provides a molded body having excellent molding processability and low volume resistivity and having small volume resistivity fluctuation regardless of thickness. The conductive liquid crystal resin composition of the present invention contains: (A) a liquid crystal resin, (B) a fibrous conductive filler, (C) a granular conductive filler, and (D) a non-conductive filler, wherein the total content of the fibrous conductive filler (B) and the granular conductive filler (C) is 25 to 50% by mass, the mass ratio of the content of the fibrous conductive filler (B) to the content of the granular conductive filler (C) is 0.50 to 3.00, and the content of the non-conductive filler (D) is 2 to 8% by mass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a conductive liquid crystal resin composition. Background Art

[0002] Liquid crystal resins represented by liquid crystal polyester resins have excellent mechanical strength, heat resistance, chemical resistance, electrical properties, etc. in a well-balanced manner, and also have excellent dimensional stability, and are therefore widely used as high-performance engineering plastics. In addition, the excellent fluidity of liquid crystal resins is effectively utilized, and conductive fillers are mixed in liquid crystal resins to impart conductivity (e.g., Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2005-187696 Summary of the invention

[0006] Problem that the invention aims to solve

[0007] In recent years, with the transition from LTE to 5G, the signal transmission speed and signal accuracy need to be greatly improved in many products such as connectors, transmission substrates, and antennas. In the development of conductive materials such as connector materials related to high-speed communications, the importance of thermoplastic conductive materials that can be given complex shapes as a noise countermeasure based on electromagnetic wave shields or grounding points is increasing. For such conductive materials, not only is the volume resistivity, which is an indicator of conductivity, low, but also excellent forming processability is sought in order to facilitate forming into complex shapes. Furthermore, after forming into a complex shape, the volume resistivity changes little regardless of the thickness of the formed body.

[0008] As a candidate for the conductive material as described above, a liquid crystal resin composition can be cited. However, according to the research of the inventors, the existing liquid crystal resin composition has a high volume resistivity and a high melt viscosity, so the molding processability is not sufficient. The present invention is made to solve the above-mentioned problems, and its purpose is to provide a conductive liquid crystal resin composition, which can give a molded body with not only excellent molding processability and low volume resistivity, but also small volume resistivity variation regardless of thickness.

[0009] Solutions for solving problems

[0010] The present inventors have conducted intensive research to solve the above problems. As a result, it was found that the above problems can be solved and the present invention was completed by using the following conductive liquid crystal resin composition, wherein the conductive liquid crystal resin composition contains: a liquid crystal resin, a fibrous conductive filler, a granular conductive filler, and a non-conductive filler, the total content of the fibrous conductive filler and the granular conductive filler is within a prescribed range, the mass ratio of the content of the fibrous conductive filler to the content of the granular conductive filler is within a prescribed range, and the content of the non-conductive filler is within a prescribed range. More specifically, the present invention provides the following composition.

[0011] (1) A conductive liquid crystal resin composition comprising:

[0012] (A) a liquid crystal resin, (B) a fibrous conductive filler, (C) a granular conductive filler, and (D) a non-conductive filler, wherein the total content of the (B) fibrous conductive filler and the (C) granular conductive filler is 25 to 50% by mass, the mass ratio of the content of the (B) fibrous conductive filler to the content of the (C) granular conductive filler is 0.50 to 3.00, and the content of the (D) non-conductive filler is 2 to 8% by mass.

[0013] (2) The conductive liquid crystal resin composition according to (1), wherein the (B) fibrous conductive filler is carbon fiber, and the (C) particulate conductive filler is carbon black.

[0014] (3) A conductive liquid crystal resin composition according to (1) or (2), wherein the non-conductive filler (D) is one or more selected from the group consisting of talc, mica, glass flakes, silica, glass beads, hollow glass microspheres, potassium titanate whiskers, calcium silicate whiskers, milled glass fibers, and glass fibers.

[0015] (4) The conductive liquid crystal resin composition according to any one of (1) to (3), wherein the non-conductive filler (D) is at least one selected from the group consisting of talc, mica, silica, and glass fiber.

[0016] Effects of the Invention

[0017] According to the present invention, there can be provided a conductive liquid crystal resin composition which provides a molded body having excellent molding processability and low volume resistivity and having small fluctuation in volume resistivity regardless of thickness. DETAILED DESCRIPTION

[0018] Hereinafter, embodiments of the present invention will be described. However, the present invention is not limited to the following embodiments.

[0019] <Conductive Liquid Crystal Resin Composition>

[0020] The conductive liquid crystal resin composition of the present invention contains (A) a liquid crystal resin, (B) a fibrous conductive filler, (C) a particulate conductive filler, and (D) a non-conductive filler.

[0021] [(A) Liquid crystal resin]

[0022] The (A) liquid crystal resin used in the present invention refers to a melt-processable polymer having the property of forming an optically anisotropic melt phase. The property of the anisotropic melt phase can be confirmed by a conventional polarization detection method using orthogonal polarizers. More specifically, the confirmation of the anisotropic melt phase can be implemented as follows: using a Leitz polarizing microscope, a molten sample mounted on a Leitz hot stage is observed under a nitrogen atmosphere at a magnification of 40 times, thereby implementing. When the liquid crystal polymer that can be applied to the present invention is detected between orthogonal polarizers, polarized light is usually transmitted even in a molten static state, showing optical anisotropy.

[0023] The type of the liquid crystalline resin (A) is not particularly limited, but is preferably an aromatic polyester and / or an aromatic polyester amide. In addition, polyesters partially containing aromatic polyesters and / or aromatic polyester amides in the same molecular chain are also within this range. As the liquid crystalline resin (A), preferably used is one having a logarithmic viscosity (IV) of at least about 2.0 dl / g, more preferably 2.0 to 10.0 dl / g, when dissolved in pentafluorophenol at a concentration of 0.1% by mass at 60°C.

[0024] The aromatic polyester or aromatic polyester amide as the (A) liquid crystalline resin applicable to the present invention is particularly preferably an aromatic polyester or aromatic polyester amide having, as a constituent component, one or more repeating units derived from aromatic hydroxycarboxylic acids and derivatives thereof.

[0025] More specifically, we can cite:

[0026] (1) Polyesters mainly comprising repeating units derived from one or more of aromatic hydroxycarboxylic acids and their derivatives;

[0027] (2) A polyester mainly comprising (a) repeating units derived from one or more kinds of aromatic hydroxycarboxylic acids and their derivatives, and (b) repeating units derived from one or more kinds of aromatic dicarboxylic acids, alicyclic dicarboxylic acids, and their derivatives;

[0028] (3) A polyester mainly comprising (a) repeating units derived from one or more kinds of aromatic hydroxycarboxylic acids and their derivatives, (b) repeating units derived from one or more kinds of aromatic dicarboxylic acids, alicyclic dicarboxylic acids, and their derivatives, and (c) repeating units derived from at least one or more kinds of aromatic diols, alicyclic diols, aliphatic diols, and their derivatives;

[0029] (4) A polyester amide mainly comprising (a) repeating units derived from one or more kinds of aromatic hydroxycarboxylic acids and their derivatives, (b) repeating units derived from one or more kinds of aromatic hydroxyamines, aromatic diamines, and their derivatives, and (c) repeating units derived from one or more kinds of aromatic dicarboxylic acids, alicyclic dicarboxylic acids, and their derivatives;

[0030] (5) Polyester amides mainly comprising (a) repeating units derived from one or more kinds of aromatic hydroxycarboxylic acids and their derivatives, (b) repeating units derived from one or more kinds of aromatic hydroxyamines, aromatic diamines, and their derivatives, (c) repeating units derived from one or more kinds of aromatic dicarboxylic acids, alicyclic dicarboxylic acids, and their derivatives, and (d) repeating units derived from at least one kind or more kinds of aromatic diols, alicyclic diols, aliphatic diols, and their derivatives. A molecular weight modifier may be used in combination with the above-mentioned components as needed.

[0031] Preferred examples of specific compounds constituting the liquid crystal resin (A) applicable to the present invention include aromatic hydroxycarboxylic acids such as 4-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid; aromatic diols such as 2,6-dihydroxynaphthalene, 1,4-dihydroxynaphthalene, 4,4'-dihydroxybiphenyl, hydroquinone, resorcinol, compounds represented by the following general formula (I), and compounds represented by the following general formula (II); aromatic dicarboxylic acids such as 1,4-phenylenedicarboxylic acid, 1,3-phenylenedicarboxylic acid, 4,4'-diphenylenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and compounds represented by the following general formula (III); aromatic amines such as p-aminophenol, p-phenylenediamine, and N-acetyl-p-aminophenol.

[0032]

[0033] (X: is a group selected from alkylene (C1-C4), alkylidene, -O-, -SO-, -SO2-, -S-, and -CO-.)

[0034]

[0035] (Y: is selected from -(CH2) n -(n=1~4) and -O(CH2)n O-(n=1 to 4).

[0036] The preparation of (A) liquid crystal resin used in the present invention can be carried out by a known method using a direct polymerization method or an ester exchange method using the above-mentioned monomer compound (or a mixture of monomers), generally using a melt polymerization method, a solution polymerization method, a slurry polymerization method, a solid phase polymerization method, or a combination of these two or more, preferably a melt polymerization method, or a combination of a melt polymerization method and a solid phase polymerization method. The above-mentioned compounds with ester-forming ability can be used directly for polymerization, and in addition, they can also be modified from a precursor to a derivative with ester-forming ability in the early stage of polymerization. When they are polymerized, various catalysts can be used. As representative catalysts, metal salt catalysts such as potassium acetate, magnesium acetate, stannous acetate, tetrabutyl titanate, lead acetate, sodium acetate, antimony trioxide, tri(2,4-pentanedione) cobalt (III), N-methylimidazole, and organic compound catalysts such as 4-dimethylaminopyridine can be cited. The amount of the catalyst is usually preferably about 0.001 to 1% by mass, particularly preferably about 0.01 to 0.2% by mass relative to the total mass of the monomer. The polymers produced by these polymerization methods can be further increased in molecular weight by a solid phase polymerization method in which the polymers are heated under reduced pressure or in an inert gas, if necessary.

[0037] The melt viscosity of the liquid crystal resin (A) obtained by the above method is not particularly limited. Generally, the melt viscosity at the molding temperature and the shear rate of 1000 sec. can be used. -1 The viscosity of the liquid crystal resin (A) is preferably 3 Pa·s or more and 500 Pa·s or less. However, when the viscosity is too high, the fluidity is greatly deteriorated, which is not preferred. It should be noted that the liquid crystal resin (A) may be a mixture of two or more liquid crystal resins.

[0038] In the conductive liquid crystal resin composition of the present invention, the content of the liquid crystal resin (A) is preferably 42 to 73% by mass, more preferably 47.3 to 67.7% by mass, and even more preferably 52.5 to 64.5% by mass. When the content of the component (A) is within the above range, fluidity, heat resistance, and the like are preferred.

[0039] [(B) Fibrous conductive filler]

[0040] The conductive liquid crystal resin composition of the present invention contains a fibrous conductive filler. The fibrous conductive filler can be used alone or in combination of two or more.

[0041] The average fiber length of the (B) fibrous conductive filler is not particularly limited. From the perspective of conductivity, it can be, for example, 50 μm or more and 10 mm or less, 80 μm or more and 8 mm or less, or 100 μm or more and 7 mm or less. It should be noted that in this specification, the average fiber length of the (B) fibrous conductive filler is as follows: 10 solid microscope images of the fibrous conductive filler are imported from a CCD camera into a PC, and an image measuring machine is used to measure the fiber length of 100 fibrous conductive fillers in each solid microscope image, i.e., a total of 1000 fibrous conductive fillers, by an image processing method. The average fiber length of the (B) fibrous conductive filler in the conductive liquid crystal resin composition is determined by applying the above method to the fibrous conductive filler remaining after the conductive liquid crystal resin composition is heated at 500°C for 4 hours and ashed.

[0042] The fiber diameter of the (B) fibrous conductive filler is not particularly limited. From the perspective of conductivity, it can be, for example, 0.2 to 15 μm, 0.25 to 13 μm, or 0.3 to 11 μm. It should be noted that in this specification, the fiber diameter of the (B) fibrous conductive filler is the average value of the values ​​obtained by observing the fibrous conductive filler using a scanning electron microscope and measuring the fiber diameter of 30 fibrous conductive fillers. The fiber diameter of the (B) fibrous conductive filler in the conductive liquid crystal resin composition is determined by applying the above method to the fibrous conductive filler remaining after the conductive liquid crystal resin composition is heated at 500°C for 4 hours and ashed.

[0043] (B) The fibrous conductive filler includes, for example, carbon fibers; conductive fibers such as metal fibers; and fibers obtained by coating an inorganic fibrous material with a metal such as nickel or copper to impart conductivity. Carbon fibers are preferred from the viewpoint of conductivity.

[0044] Examples of the carbon fiber include PAN-based carbon fibers made from polyacrylonitrile as a raw material and pitch-based carbon fibers made from pitch as a raw material.

[0045] Examples of the metal fibers include fibers made of mild steel, stainless steel, steel and its alloys, copper, brass, aluminum and its alloys, titanium, lead, etc. These metal fibers may be coated with other metals to further impart conductivity, if necessary, depending on their conductivity.

[0046] Examples of the inorganic fibrous material include glass fiber, milled glass fiber, asbestos fiber, silica fiber, silica / alumina fiber, zirconia fiber, boron nitride fiber, silicon nitride fiber, boron fiber, potassium titanate whisker, calcium silicate whisker (fibrous wollastonite), and the like.

[0047] [(C) Granular conductive filler]

[0048] The conductive liquid crystal resin composition of the present invention contains a particulate conductive filler. The particulate conductive filler can be used alone or in combination of two or more.

[0049] (C) The median particle size of the particulate conductive filler is not particularly limited, and from the viewpoint of conductivity, it may be, for example, 10 nm or more and 50 μm or less, 15 nm or more and 20 μm or less, or 18 nm or more and 10 μm or less. It should be noted that in this specification, the median particle size refers to the volume-based central value measured by a laser diffraction / scattering particle size distribution measurement method.

[0050] As (C) granular conductive fillers, carbon black, granular metal powder (such as aluminum, iron, copper), granular conductive ceramics (such as zinc oxide, tin oxide, indium tin oxide), etc. can be cited. From the viewpoint of conductivity, carbon black is preferred. Carbon black is not particularly limited if it is commonly used for resin coloring and can be obtained. Usually, carbon black contains agglomerates formed by the aggregation of primary particles, but as long as it does not obviously contain a large number of agglomerates of 50 μm or more in size, it is difficult to produce many bumps (fine bump-like protrusions (fine bumps and depressions) formed by the aggregation of carbon black) on the surface of the molded body formed by the resin composition of the present invention. If the content rate of the particles with a particle size of 50 μm or more of the above-mentioned agglomerates is less than 20 ppm, the smoothness of the surface of the molded body tends to increase. The preferred content rate is less than 5 ppm.

[0051] In the conductive liquid crystal resin composition of the present invention, the total content of the fibrous conductive filler (B) and the granular conductive filler (C) is 25 to 50% by mass, preferably 29 to 45% by mass, and more preferably 33 to 40% by mass. If the total content is 25% by mass or more, the volume resistivity of the molded body is easily reduced, and a molded body with improved conductivity is easily obtained. If the total content is 50% by mass or less, the fluidity of the conductive liquid crystal resin composition is easily improved, and a conductive liquid crystal resin composition with excellent molding processability is easily obtained.

[0052] The mass ratio of the content of the aforementioned (B) fibrous conductive filler to the content of the aforementioned (C) granular conductive filler is 0.50 to 3.00, preferably 0.60 to 2.50, and more preferably 0.70 to 2.00. If the above mass ratio is 0.50 or more, the fluidity of the conductive liquid crystal resin composition is easily improved, and a conductive liquid crystal resin composition with excellent molding processability is easily obtained, and the thickness dependence of the conductivity of the molded body is easily reduced, and a molded body with a small change in volume resistivity regardless of thickness is easily obtained. If the above mass ratio is 3.00 or less, the thickness dependence of the conductivity of the molded body is easily reduced, and a molded body with a small change in volume resistivity regardless of thickness is easily obtained.

[0053] [(D) Non-conductive filler]

[0054] The conductive liquid crystal resin composition of the present invention contains a non-conductive filler. The non-conductive filler can be used alone or in combination of two or more. Examples of the (D) non-conductive filler include plate-like non-conductive fillers, granular non-conductive fillers, and fibrous non-conductive fillers.

[0055] The median particle size of the plate-like non-conductive filler is not particularly limited, and may be, for example, 10 to 100 μm, 12 to 50 μm, or 14 to 30 μm. If the median particle size of the plate-like non-conductive filler is 10 to 100 μm, the thickness dependence of the conductivity of the molded body is easily reduced, and a molded body with a small change in volume resistivity regardless of thickness is easily obtained. Examples of the plate-like non-conductive filler include talc, mica, and glass flakes.

[0056] The median particle size of the granular non-conductive filler is not particularly limited, and may be, for example, 0.3 to 50 μm, 0.4 to 25 μm, or 0.5 to 5.0 μm. If the median particle size of the granular non-conductive filler is 0.3 to 50 μm, the thickness dependence of the conductivity of the molded body is easily reduced, and a molded body with a small change in volume resistivity regardless of thickness is easily obtained. Examples of granular non-conductive fillers include silicates such as silicon dioxide, quartz powder, glass beads, hollow glass microspheres, glass powder, calcium silicate, aluminum silicate, kaolin, clay, diatomaceous earth, and wollastonite; metal oxides such as iron oxide, titanium oxide, zinc oxide, and aluminum oxide; metal carbonates such as calcium carbonate and magnesium carbonate; metal sulfates such as calcium sulfate and barium sulfate; silicon carbide; silicon nitride; boron nitride, and the like.

[0057] The average fiber length of the fibrous non-conductive filler is not particularly limited, and may be, for example, 50 μm or more and 10 mm or less, 80 μm or more and 7 mm or less, or 100 μm or more and 4 mm or less. If the average fiber length of the fibrous non-conductive filler is 50 μm or more and 10 mm or less, the thickness dependence of the conductivity of the molded body is easily reduced, and a molded body with a small change in volume resistivity regardless of thickness is easily obtained. The fiber diameter of the fibrous non-conductive filler is not particularly limited, and may be, for example, 0.2 to 15 μm, 0.25 to 13 μm, or 0.3 to 11 μm. If the fiber diameter of the fibrous non-conductive filler is 0.2 to 15 μm, the thickness dependence of the conductivity of the molded body is easily reduced, and a molded body with a small change in volume resistivity regardless of thickness is easily obtained. As the average fiber length of the fibrous non-conductive filler and the fiber diameter of the fibrous non-conductive filler, the average value of the values ​​measured in the same manner as described above in (B) the fibrous conductive filler is used. Examples of fibrous non-conductive fillers include inorganic fibrous substances such as glass fibers, milled glass fibers, asbestos fibers, silica fibers, silica / alumina fibers, zirconia fibers, boron nitride fibers, silicon nitride fibers, boron fibers, potassium titanate whiskers, and calcium silicate whiskers (fibrous wollastonite).

[0058] Since the thickness dependence of the conductivity of the molded body is more easily reduced and a molded body with little variation in volume resistivity regardless of thickness is more easily obtained, the (D) non-conductive filler is preferably one or more selected from the group consisting of talc, mica, glass flakes, silica, glass beads, hollow glass microspheres, potassium titanate whiskers, calcium silicate whiskers, milled glass fibers, and glass fibers, more preferably one or more selected from the group consisting of talc, mica, silica, and glass fibers, and even more preferably one or more selected from the group consisting of talc, mica, and silica.

[0059] In the conductive liquid crystal resin composition of the present invention, the content of the non-conductive filler (D) is 2 to 8% by mass, preferably 2.3 to 7.7% by mass, and more preferably 2.5 to 7.5% by mass. When the content is 2 to 8% by mass, the fluidity of the conductive liquid crystal resin composition is easily improved, and a conductive liquid crystal resin composition with excellent molding processability is easily obtained.

[0060] [Other ingredients]

[0061] In the range that does not damage the effect of the present invention, the liquid crystal resin composition of the present invention can be suitably added with other polymers, other fillers, known substances usually added to synthetic resins according to the required performance, that is, stabilizers such as antioxidants, ultraviolet absorbers, antistatic agents, flame retardants, dyes, pigments, colorants, lubricants, crystallization accelerators, crystallization nucleating agents, release agents and other components. Other components can be used alone or in combination of two or more.

[0062] Examples of the other polymer include epoxy group-containing copolymers. The other polymers may be used alone or in combination of two or more.

[0063] Other fillers refer to fillers other than (B) fibrous conductive fillers, (C) granular conductive fillers, and (D) non-conductive fillers, and examples thereof include conductive fillers other than components (B) and (C). Other fillers may be used alone or in combination of two or more. As conductive fillers other than components (B) and (C), for example, plate-like conductive fillers may be used.

[0064] [Method for preparing conductive liquid crystal resin composition]

[0065] The preparation method of the conductive liquid crystal resin composition of the present invention is not particularly limited. For example, the conductive liquid crystal resin composition is prepared by mixing the above-mentioned components (A) to (D) and at least one of any other components, and performing melt kneading treatment on them using a single-screw or twin-screw extruder.

[0066] [Conductive liquid crystal resin composition]

[0067] For the conductive liquid crystal resin composition of the present invention obtained as described above, the melt viscosity is preferably 150 Pa·sec or less, more preferably 145 Pa·sec or less, and even more preferably 140 Pa·sec or less, from the viewpoint of fluidity when melted and the viewpoint of molding processability. In this specification, the melt viscosity is the value obtained as follows: at a barrel temperature 10 to 20°C higher than the melting point of the liquid crystal resin, a shear rate of 1000 sec -1 The value is obtained according to the measurement method of ISO 11443 under the conditions of .

[0068] <Conductive Materials>

[0069] The conductive liquid crystal resin composition of the present invention can be used to manufacture a conductive material. The conductive material of the present invention is made from a molded body of the conductive liquid crystal resin composition of the present invention. The conductive material of the present invention not only has a low volume resistivity, but also has a small change in volume resistivity regardless of thickness. Therefore, the conductive material of the present invention can be suitably used for products with complex shapes having various thicknesses, specifically, can be used for example, connectors, transmission substrates, antennas, etc.

[0070] Example

[0071] The present invention will be further described in detail with reference to the following examples, but the present invention is not limited to these examples.

[0072] <Liquid Crystal Resin>

[0073] Liquid crystal polyester amide resin

[0074] After the following raw materials are added to the polymerization container, the temperature of the reaction system is raised to 140°C and reacted at 140°C for 1 hour. After that, the temperature is further raised to 340°C in 4.5 hours, and then the pressure is reduced to 10Torr (i.e., 1330Pa) in 15 minutes, and melt polymerization is carried out while distilling acetic acid, excess acetic anhydride, and other low-boiling components. After the stirring torque reaches the specified value, nitrogen is introduced and the pressure is changed from the reduced pressure state to the normal pressure state, and the polymer is discharged from the lower part of the polymerization container, and the strands are granulated to obtain pellets. The obtained pellets are heat treated at 300°C for 2 hours under a nitrogen gas flow to obtain the target polymer. The melting point of the obtained polymer is 336°C, and the melt viscosity at 350°C is 19.0Pa·s. It should be noted that the melting point of the above-mentioned polymer is measured according to the melting point determination method described later, and the melt viscosity of the above-mentioned polymer is measured in the same way as the melt viscosity determination method described later.

[0075] (I) 4-Hydroxybenzoic acid (HBA); 1380 g (60 mol%)

[0076] (II) 2-Hydroxy-6-naphthoic acid (HNA); 157 g (5 mol%)

[0077] (III) 1,4-phenylenedicarboxylic acid (TA); 484 g (17.5 mol%)

[0078] (IV) 4,4'-dihydroxybiphenyl (BP); 388 g (12.5 mol%)

[0079] (V) N-acetyl-p-aminophenol (APAP); 126 g (5 mol%)

[0080] Metal catalyst (potassium acetate catalyst); 110 mg

[0081] Acylating agent (acetic anhydride); 1659 g

[0082] <Materials other than liquid crystal resin>

[0083] · Fibrous conductive filler: HTC432 manufactured by Teijin Limited (PAN-based carbon fiber, chopped strands, fiber diameter 7 μm, length 6 mm)

[0084] Carbon black: VULCAN XC305 (produced by Cabot Japan Co., Ltd., median particle size 20 nm, proportion of particles with a particle size of 50 μm or more is 20 ppm or less)

[0085] Talc: CROWN TALC PP (manufactured by Matsumura Sangyo Co., Ltd., talc, median particle size 14.6 μm)

[0086] · Mica: AB-25S (manufactured by YAMAGUCHI MICA CO., LTD., mica, median particle size 25.0 μm)

[0087] Silica: Denka fused silica FB-5SDC (manufactured by Denka Corporation, silica, median particle size 4.0 μm)

[0088] Glass fiber: ECS03T-786H (manufactured by Nippon Electric Glass Co., Ltd., chopped strands, fiber diameter 10 μm, length 3 mm)

[0089] [Method for determining melting point]

[0090] Using a DSC manufactured by TA Instruments, the endothermic peak temperature (Tm1) observed when the liquid crystal resin was heated from room temperature at a heating condition of 20°C / min was measured, and then the temperature was maintained at (Tm1+40)°C for 2 minutes, and then the liquid crystal resin was cooled to room temperature at a cooling condition of 20°C / min, and then the endothermic peak temperature observed when the liquid crystal resin was heated again at a heating condition of 20°C / min was measured.

[0091] <Manufacturing of Conductive Liquid Crystal Resin Composition>

[0092] The above components were melt-kneaded at a barrel temperature of 350° C. using a twin-screw extruder (TEX30α model manufactured by The Nippon Steel Works, Ltd.) in the proportions shown in Table 1 or 2 (unit: mass %) to obtain conductive liquid crystal resin composition pellets.

[0093] <Melt Viscosity>

[0094] The melt viscosity of the conductive liquid crystal resin composition was measured using a Capilograph 1B manufactured by Toyo Seiki Seisaku-sho Co., Ltd. at a temperature 10 to 20°C higher than the melting point of the liquid crystal resin, using an orifice with an inner diameter of 1 mm and a length of 20 mm, at a shear rate of 1000 / sec in accordance with ISO11443. It should be noted that the measurement temperature was 350°C. The results are shown in Tables 1 and 2.

[0095] <Volume Resistivity>

[0096] The pellets of the examples and comparative examples were formed using a forming machine ("SE100DU" manufactured by Sumitomo Heavy Industries, Ltd.) under the following forming conditions to obtain a flat test piece 1 of 80 mm × 80 mm × 1 mmt or a flat test piece 2 of 80 mm × 80 mm × 2 mmt. Using the flat test piece 1, the volume resistivity (hereinafter also referred to as "1 mmt volume resistivity") was measured using a resistivity meter ("Loresta-GP" manufactured by Nittoseiko Analytech Co., Ltd.) in accordance with JIS K 7194. In addition, using the flat test piece 2, the volume resistivity (hereinafter also referred to as "2 mmt volume resistivity") was measured using a resistivity meter ("Loresta-GP" manufactured by Nittoseiko Analytech Co., Ltd.) in accordance with JIS K 7194. Furthermore, the difference between the 1 mmt volume resistivity and the 2 mmt volume resistivity was calculated. The results are shown in Tables 1 and 2. When the absolute value of the difference is 0.10 Ω·cm or less, it is evaluated that the variation in volume resistivity is small regardless of the thickness.

[0097] [Forming conditions]

[0098] Barrel temperature: 350℃

[0099] Mold temperature: 80℃

[0100] Injection speed: 33mm / sec

[0101] [Table 1]

[0102]

[0103] [Table 2]

[0104]

[0105] The results shown in Tables 1 and 2 show that the compositions of Examples have low melt viscosity and high fluidity, and therefore have excellent moldability. It is also confirmed that the molded bodies obtained from the compositions of Examples have low volume resistivity and small variations in volume resistivity regardless of thickness.

Claims

1. A conductive liquid crystal resin composition comprising: (A) a liquid crystal resin, (B) a fibrous conductive filler, (C) a granular conductive filler, and (D) a non-conductive filler, The total content of the (B) fibrous conductive filler and the (C) granular conductive filler is 25 to 50% by mass. The mass ratio of the content of the (B) fibrous conductive filler to the content of the (C) granular conductive filler is 0.50 to 3.00, The content of the (D) non-conductive filler is 2 to 8% by mass. The (D) non-conductive filler is one or more selected from the group consisting of talc, mica, silica and glass fiber.

2. The conductive liquid crystal resin composition according to claim 1, wherein The (B) fibrous conductive filler is carbon fiber, and the (C) granular conductive filler is carbon black.

Citation Information

Patent Citations

  • Conductive resin composition

    JP2005187696A

  • Liquid crystal polymer resin composition

    JP1992311758A